Protein-protein interactions in plant antioxidant defense - Melicher, Pavol; Dvořák, Petr; Šamaj, Jozef; Takáč, Tomáš (Frontiers in Plant Science, 2022)
The regulation of ROS levels in plants is ensured by mechanisms preventing their over accumulation, and by diverse antioxidants, including enzymes and nonenzymatic compounds. These are affected by redox conditions, posttranslational modifications, transcriptional and posttranscriptional modifications, Ca2+, NO and mitogen-activated protein kinase signaling pathways. Recent knowledge about protein-protein interactions of antioxidant enzymes advanced during last decade. The best-known examples are interactions mediated by redox buffering proteins such as thioredoxins and glutaredoxins. This review summarizes interactions of major antioxidant enzymes with regulatory and signaling proteins and their diverse functions. Such interactions are important for stability, degradation and activation of interacting partners. Moreover, protein-protein interactions of antioxidant enzymes may connect diverse metabolic processes with ROS scavenging. Proteins like receptor for activated C kinase 1 may ensure coordination of more antioxidant enzymes to ensure efficient ROS regulation. Nevertheless, protein-protein interactions in antioxidant defense are understudied, and intensive research is required to define their role in complex regulation of ROS scavenging.